Who Makes an Effort? A Person-Centered Examination of Motivation and Beliefs as Predictors of Students’ Effort and Performance on the PISA 2015 Science Assessment - Hofverberg, Anders; Eklöf, Hanna; Lindfors, Maria (Frontiers in Education, 2022)
Each time new PISA results are presented, they gain a lot of attention. However, there are many factors that lie behind the results, and they get less attention. In this study, we take a person-centered approach and focus on students’ motivation and beliefs, and how these predict students’ effort and performance on the PISA 2015 assessment of scientific literacy. Moreover, we use both subjective (self-report) and objective (time-based) measures of effort, which allows us to compare these different types of measures. Latent profile analysis was used to group students in profiles based on their instrumental motivation, enjoyment, interest, self-efficacy, and epistemic beliefs (all with regard to science). A solution with four profiles proved to be best. When comparing the effort and performance of these four profiles, we saw several significant differences, but many of these differences disappeared when we added gender and the PISA index of economic, social, and cultural status (ESCS) as control variables. The main difference between the profiles, after adding control variables, was that the students in the profile with most positive motivation and sophisticated epistemic beliefs performed best and put in the most effort. Students in the profile with unsophisticated epistemic beliefs and low intrinsic values (enjoyment and interest) were most likely to be classified as low-effort responders. We conclude that strong motivation and sophisticated epistemic beliefs are important for both the effort students put into the PISA assessment and their performance, but also that ESCS had an unexpectedly large impact on the results.